2017
DOI: 10.1111/1753-0407.12522
|View full text |Cite
|
Sign up to set email alerts
|

Association of type 2 diabetes mellitus with the interaction between low‐density lipoprotein receptor‐related protein 5 (LRP5) polymorphisms and overweight and obesity in rural Chinese adults

Abstract: Background: Low-density lipoprotein receptor-related protein 5 (LRP5) plays an important role in glucose and cholesterol metabolism. The present cohort study evaluated associations of LRP5 variants with the incidence of type 2 diabetes mellitus (T2DM) in a rural adult Chinese population. Methods: In all, 7751 subjects aged ≥18 years without T2DM underwent genotyping at baseline; 6326 subjects (81.62%) were followed-up, and 5511 with a clear disease outcome were eligible for analysis. The same questionnaire was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Polymorphisms in the potassium voltage-gated channel subfamily B member 1 may be associated with insulin resistance ( 32 ), the protein coded by tea shirt zinc finger homeobox 1 regulates β-cell maturation ( 33 ), and alleles in JAZ zinc finger 1 reveal differential transcription specifically in the pancreatic tissue ( 34 ). Clearly linked to lipid metabolism, numerous polymorphisms in LDL receptor protein 5 are associated with obesity and body composition ( 35 , 36 ). Moreover, an overlap has been observed between these categories (i.e., glucose control, insulin sensitivity and obesity), and several of these genes presumably exhibit coordinated functions involving multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in the potassium voltage-gated channel subfamily B member 1 may be associated with insulin resistance ( 32 ), the protein coded by tea shirt zinc finger homeobox 1 regulates β-cell maturation ( 33 ), and alleles in JAZ zinc finger 1 reveal differential transcription specifically in the pancreatic tissue ( 34 ). Clearly linked to lipid metabolism, numerous polymorphisms in LDL receptor protein 5 are associated with obesity and body composition ( 35 , 36 ). Moreover, an overlap has been observed between these categories (i.e., glucose control, insulin sensitivity and obesity), and several of these genes presumably exhibit coordinated functions involving multiple mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases are independently known to cause serious health complications, with risks of cardiovascular diseases, 2 of 13 higher mortality, low quality of life, and increased public health spending; however, when these disease occur concurrently, their negative effects on health, health systems, and mortality are even greater [1,3,4]. There are few studies on T2DM in obese individuals [5,6], and even fewer on those with higher obesity levels, such as class II and III [7]. The few studies on T2DM associated with higher obesity classes are related to surgical procedures [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies have shown that the relationship between obesity and T2DM was also affected by other factors, such as a study that found an interaction between autoimmune thyroid disease and obesity in patients with T2DM 28 . A study of a Chinese rural population showed that low‐density lipoprotein receptor‐related protein 5 (LRP5) polymorphisms also interacted with obesity in T2DM, and LRP5 polymorphisms are associated with beta‐cell function and lipid metabolism 29 . In addition, obesity and COVID‐19 interacted in the pathogenesis of diabetes 30 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 A study of a Chinese rural population showed that low‐density lipoprotein receptor‐related protein 5 (LRP5) polymorphisms also interacted with obesity in T2DM, and LRP5 polymorphisms are associated with beta‐cell function and lipid metabolism. 29 In addition, obesity and COVID‐19 interacted in the pathogenesis of diabetes. 30 However, the evidence for the interaction of obesity and HR in the onset of T2DM was relatively lacking, with only one study on a rural population in Tongxiang, Zhejiang, China.…”
Section: Discussionmentioning
confidence: 99%